2006
DOI: 10.1029/2006eo190001
|View full text |Cite
|
Sign up to set email alerts
|

Yangtze sediment decline partly from Three Gorges Dam

Abstract: It could be argued that nowhere has the impact of dams on rivers been more important than in China, where since 1950 almost half of the world's large dams (higher than 15 meters) have been built ]Fuggle and Smith, 2000]. China's Yangtze River (Changjiang)—the largest river in south Asia (1.8 million square kilometers) and whose basin is home to more than 400 million inhabitants—alone has more than 50,000 dams within its watershed, including the world's largest, the Three Gorges Dam (TGD) (Figure 1a ). Water an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 2 publications
1
70
0
Order By: Relevance
“…1) are the largest rivers in North America and Asia, respectively. Their geological and hydrological conditions and geomorphological evolution have previously been reported for the Mississippi River (Meade et al, 1995;Colman et al, 1998;Roberts, 1998;Day et al, 2007;Bianchi & Allison, 2009;Blum & Roberts, 2009;Horowitz, 2009;Meade & Moody, 2010;Allison et al, 2012) and the Yangtze River (Chen et al, 2001;Yang et al, 2002;Xu et al, 2006;Yang et al, 2006;Xu & Milliman, 2009;Yang et al, 2011). However, only a few papers have directly compared these two rivers (Xu et al, 2007;Bianchi & Allison, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) are the largest rivers in North America and Asia, respectively. Their geological and hydrological conditions and geomorphological evolution have previously been reported for the Mississippi River (Meade et al, 1995;Colman et al, 1998;Roberts, 1998;Day et al, 2007;Bianchi & Allison, 2009;Blum & Roberts, 2009;Horowitz, 2009;Meade & Moody, 2010;Allison et al, 2012) and the Yangtze River (Chen et al, 2001;Yang et al, 2002;Xu et al, 2006;Yang et al, 2006;Xu & Milliman, 2009;Yang et al, 2011). However, only a few papers have directly compared these two rivers (Xu et al, 2007;Bianchi & Allison, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…3) (Yang et al, 2010). Dam construction, soil-conservation and decline of precipitation in the high-sediment-yield Yangtze upstream have decreased the Yangtze sediment discharge from 480 Mt/year (1953)(1954)(1955)(1956)(1957)(1958)(1959)(1960)(1961)(1962)(1963) to about 150 Mt/year in recent years (Xu et al, 2006;Yang et al, 2011). In contrast to a sharp decline in sediment production in the Mississippi (Fig.…”
Section: The Yangtze Rivermentioning
confidence: 99%
“…Xu et al [2006] found that the sediment flux from the Changjiang has decreased since 1950, independently of the long-term Changjiang discharge variation. Previous studies have investigated the long-term variation of nutrient concentration and composition [e.g., Chai et al, 2006;Li et al, 2007], but they mostly covered the region around the Changjiang, its estuary, and its adjacent waters.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last several decades, China has experienced rapid increases in chemical fertilizer use and human population (Xing and Zhu 2002;Yan et al 2003). During this same period, thousands of dams have been constructed for the triple functions of energy production (hydrological plants), agricultural irrigation, and flood control (Yang et al 2004;Xu et al 2006). The constructions of the Gezhouba Dam and Three-Gorges Dam on the mainstream of the Changjiang River (Yangtze River) in recent years have caused drastic reductions in sediment fluxes (Xu et al 2006) and a shift in the phytoplankton species in East China Sea (Gong et al 2006).…”
Section: Introductionmentioning
confidence: 99%